Choosing Andersen over Disney : challenging conventional perceptions of fairy tales - Pang, Edna Hui Qi (2014)
Fairy tales have long been regarded as a genre specifically for children’s consumption, causing most adults to mistakenly conclude that fairy tales have little to offer them aside from entertainment value. It is a mindset prevalent among contemporary audiences especially given the popularity of Disney’s adaptations of fairy tales. This is a significant problem because Disney has generally misrepresented the original fairy tales to such a degree that the Disney versions have replaced the fairy tale narrative in the public imagination. Disney’s adaptations have become so entrenched in popular culture that people unwittingly accept them as the original fairy tales themselves and as a result, this has prompted most to be dismissive of the genre’s value. This thesis seeks to counter this fallacy and instead petitions for the reversion back to the original fairy tale narratives rather than taking the Disney films as a model of the literary genre as the intrinsic human qualities embodied in the originals are filtered out in Disney’s versions.